Recovery of overdue tax payment in case of transfer of companies – regulation and problems - Klikičs, Toms (Riga Graduate School of Law, 2023)
This thesis research how company transfers get evaluated in situations involving tax debt collection in the Republic of Latvia. Differences in techniques when evaluating the facts in public law and private law and if company transfer in bad faith to avoid taxes are thoroughly examined. The author of this work underlines the importance of focusing on the substance in each case when transfer of company is spotted, not the form. The author states, that bona fide taxpayers are exposed to risks because of the inconsistent decision makings by the institutions and failure to consider all facts of each individual case. To ensure well-structured and uniform approach among deciding authorities, the author of the research, suggests developing and implement a standard of evidence needed based on jurisprudence and legal concepts. The thesis also states how important it is to defend entrepreneurs by having a thorough analysis and upholding the legal trust concept.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Tax law; company transfer